A Contemporary Perspective on Transactional Analysis Group Therapy. (3rd July 2018) - Tangolo, Anna Emanuela; Massi, Anna
Abstract: This article, written by therapists who use group therapy as the context for engaging in the deconfusion process with patients, explains why group therapy can be a setting of choice for depth psychodynamic therapy. It describes the methods and techniques used by the authors in both clinical and training settings. The strategic path outlined is aimed at allowing patients to redecide their script system for a happier and healthier life by using transference analysis, interpretative techniques, dreamwork techniques, and emotional literacy as well as implicit relational learning experiences.